PUBLIC SATISFACTION STUDY ON THE DIGITAL TRANSFORMATION OF THE PUBLIC SERVICE SYSTEM DURING THE COVID-19 PANDEMIC (2019-2021) - Bambang Arwanto (Green Publisher, 2022)
The implementation of the digital licensing system since 2018 in Indonesia through the OSS (online single submission) platform has fundamentally changed the licensing system in Indonesia, manual public services have been transformed into digital public services by merging 16 public service sectors in 18 ministries to the local government unified through a system OSS, this digital transformation of public services initially caused many problems, especially the limitations of local digital service infrastructure throughout Indonesia, but the preparation of this digital service provided a valuable lesson after the arrival of the Covid-19 pandemic, Indonesian people began to adapt to using digital public services, so that public services did not constrained even in a state of restrictions on community social activities due to the pandemic. This study uses a survey method to all people who use digital public services, to measure the level of public satisfaction with the transformation of digital services in Indonesia amid the preparation of digital public service facilities and infrastructure which are still limited and have not synchronized digital service applications used by the central and local governments. The research approach used is an exploratory case study on the level of satisfaction of public services in Kutai Kartanegara Regency in 2019-2021. Measurement of public services during the pandemic (2019-2021) shows a public satisfaction index with a value of 93.25 in the period before the pandemic (2019) and at the end of the pandemic (2021) with an index value of 90.03, the results of the study show public satisfaction in the restrictions social activities on pandemic era has a very good scale (A), this is because the public has been able to adapt for digital public services so as to make public services during the pandemic more efficient, effective, fast and easily accessible without the constraints of social restrictions.